2020
DOI: 10.1186/s13071-020-04491-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of various endogenous and exogenous factors to the mosquito microbiota

Abstract: Background The commensal microbiota of mosquitoes impacts their development, immunity, and competency, and could provide a target for alternative entomological control approaches. However, despite the importance of the mosquito/microbiota interactions, little is known about the relative contribution of endogenous and exogenous factors in shaping the bacterial communities of mosquitoes. Methods We used a high-throughput sequencing-based assay to cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The fixation of the kdr east mutation in the population also precluded further analysis of any associations between kdr alleles and the mosquito microbiota. Indeed, a recent study identified no links between the two [ 42 ]. The authors thus hypothesize that any microbe-mediated mechanism of insecticide resistance would be largely distinct from the mosquito host’s genetics, and likely of a metabolic nature.…”
Section: Discussionmentioning
confidence: 99%
“…The fixation of the kdr east mutation in the population also precluded further analysis of any associations between kdr alleles and the mosquito microbiota. Indeed, a recent study identified no links between the two [ 42 ]. The authors thus hypothesize that any microbe-mediated mechanism of insecticide resistance would be largely distinct from the mosquito host’s genetics, and likely of a metabolic nature.…”
Section: Discussionmentioning
confidence: 99%
“…Digestion and detoxification are results of different interactions between the mosquito and the symbiotic microorganisms that can influence the mosquito development and adult nutritional reserves [ 28 ]. Environmental and genetic factors, such as the location of mosquito collection [ 31 , 32 ], the mosquito species [ 33 ], and the rearing conditions [ 34 ], are considered important drivers that shape gut microbiota composition.…”
Section: Mosquito Microbiota and Environmental Factorsmentioning
confidence: 99%
“…gambiae . At the same time, adult mosquitoes can transmit symbionts in breeding water, thus influencing the microbial composition of the aquatic environment [ 32 , 44 ].…”
Section: Mosquito Microbiota and Environmental Factorsmentioning
confidence: 99%
“…Additionnally, endosymbionts are inherited from the mother to the egg. Microorganisms thriving in water are recruited by larvae, resulting in more dissimilarity in bacterial community composition in larvae from different collection sites than in larvae collected from the same site 8,9 . Moreover, microbial community structure and evolution are sensitive to biological and physico-chemical properties of the water and the microbial diversity in place 4,7,[10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, microbial community structure and evolution are sensitive to biological and physico-chemical properties of the water and the microbial diversity in place 4,7,[10][11][12] . Landuse and geographiccal positions were then associated to microbiota structure in the environment and in mosquitoes, most likely the consequence of a cascade effect 7,8,13,14 .…”
Section: Introductionmentioning
confidence: 99%